THE MEANING AND TRANSLATION PROBLEMS OF PHRASEOLOGICAL UNITS - Rustamova Sevara Farxodovna (International Engineering Journal For Research & Development, 2023)
The article is devoted to the peculiarities of the translation of phraseological units. The article presents theoretical materials on possible difficulties and ways of translating phraseological units, as well as an analysis of the main methods of translating phraseological units from the source language into another language. Theoretical reasoning is supported by examples of materials from dictionary entries of the Uzbek-English and English-Uzbek phraseological dictionaries, illustrating new methods that make it possible to adequately translate “non-equivalent” Uzbek phraseological units. The relevance of the article is explained by the active use of phraseological units in texts of different genres and, as a result, the problems of their adequate translation. The theoretical significance and practical value lies in the fact that the study of the features of the translation of phraseological units contributes to a deeper understanding and, consequently, the correct translation of phraseological units into another language. Research methods: comparison, analysis, phraseological identification method.